2017
DOI: 10.1128/aem.01302-17
|View full text |Cite
|
Sign up to set email alerts
|

Francisella-Like Endosymbionts and Rickettsia Species in Local and Imported Hyalomma Ticks

Abstract: Hyalomma ticks (Acari: Ixodidae) are hosts for Francisella-like endosymbionts (FLE) and may serve as vectors of zoonotic disease agents. This study aimed to provide an initial characterization of the interaction between Hyalomma and FLE and to determine the prevalence of pathogenic Rickettsia in these ticks. Hyalomma marginatum, Hyalomma rufipes, Hyalomma dromedarii, Hyalomma aegyptium, and Hyalomma excavatum ticks, identified morphologically and molecularly, were collected from different hosts and locations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 70 publications
9
50
0
Order By: Relevance
“…This species prefers steppe and desert climates [ 24 ], which may explain its restriction to this specific farm. Hyalomma rufipes vectors CCHF and several Rickettsia and Babesia species, and has been found on migratory birds in Israel and elsewhere [ 4 , 24 , 33 ]. Only five Hy.…”
Section: Discussionmentioning
confidence: 99%
“…This species prefers steppe and desert climates [ 24 ], which may explain its restriction to this specific farm. Hyalomma rufipes vectors CCHF and several Rickettsia and Babesia species, and has been found on migratory birds in Israel and elsewhere [ 4 , 24 , 33 ]. Only five Hy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is now well established that TBPs coexist with many other microorganisms (microbiota) in ticks constituting a tick microbial complex recently named pathobiome [32]. The microbial communities of several tick species of the genera Ixodes, Dermacentor, Hyalomma, Haemaphysalis, Rhipicephalus and Amblyomma have been studied [33][34][35][36][37][38][39] improving our knowledge on the diversity and composition of the tick microbiome. Microbiome often consists of endosymbionts, which can have multiple detrimental, neutral, or beneficial effects to their tick hosts [40,41], and therefore might play various roles in fitness, nutritional adaptation, development, reproduction, defence against environmental stress, and immunity [42].…”
Section: Introductionmentioning
confidence: 99%
“…While a few CLE and FLE strains have coevolved with their tick hosts ( Duron et al. 2017 ; Azagi et al. 2017 ), a comprehensive survey of 81 species of hard and soft ticks showed that FLEs in several soft ticks were more closely related to FLEs in hard ticks than to each other, suggesting that FLEs have been exchanged between hard and soft ticks ( Duron et al.…”
Section: Introductionmentioning
confidence: 99%